Pengaruh Rasio Keuangan Dan Pertumbuhan Perusahaan Terhadap Devidend Payout Rasio (Dpr) Dan Implikasinya Pada Harga Saham: (Studi pada Perusahaan Perbankan Yang Listing di Bursa Efek Indonesia) - Ulfah, Ulfah; Alwi, Alwi; Muniarty, Puji (PT. Alahyan Publisher Sukabumi, 2023)
This research was conducted at Banking companies listed on the Indonesia Stock Exhange (IDX). With the aim of research is to find out the effect of financial ratios and company growth on the deviation end payout ratio (DPR) and its implications for stock price in banking companies listed on the Indonesian Stock Exchange (IDX). This research is an associative research. The population in this research are 46 banking companies listed on the Indonesia Stock Exchange (IDX). The samples in this study amounted to four banks. The sampling technique used is purposive sampling. This research uses secondary data using the data analysis method Classical assumption test (consisting of normality test, multicollinearity test, autocorrelation test and heteroscedasticity test), multiple linear regression analysis, partial test (t-test), and path analysis with the help of the SPSS version. 20. The results of this study indicate that ROA (Return On Assets), DER (Debt to Equity Ratio), and Company Growth has no significant effect on the DPR (Devidend Payout Ratio). Furthermore, the DPR has no significant effect on stock prices, while ROA and DER have no significant effect on stock prices through the DPR (Devidend Payout Ratio), and Company Growth has a significant effect on stock prices through the DPR (Devidend Payout Ratio).